Nonreciprocity: Nonreciprocal Magnetic Coupling Using Nonlinear Meta‐Atoms (Adv. Sci. 19/2020) - Zhao, Xiaoguang (Adv Sci (Weinh), 2020)
In article number 2001443, Stephan W. Anderson, Xin Zhang, and co‐workers demonstrate a nonreciprocal system based on the linear and nonlinear meta‐atoms. Theoretical studies and experiments reveal the bounds of the nonreciprocity based on the passive and nonlinear resonators. The paradigm may be employed to construct magnetless radiofrequency isolators and other nonreciprocal devices. [Image: see text]